Secured Low Power Overhead Compensator Look-Up-Table (LUT) Substitution Box (S-Box) Architecture - Pammu, Ali Akbar (2017)
Substitution-Box (S-Box) is an important security building block for the Advanced Encryption Standard (AES) algorithm. However, its high power dissipation always compromises with its security feature under Correlation Power Analysis (CPA) attack. In this paper, we propose a secured and low power overhead LUT based S-Box architecture embodying a novel multiplexing circuit AND and OR a compensator. We achieve these attributes as follows. First, we employ AND and OR gates to realize the multiplexing circuit therein in a regular structure to minimize the delay and power variations for every input pattern, hence mitigating the security risk against CPA. Second, we augment a compensator to complement the multiplexing circuit to further minimize the power variations within the LUT based S-Box. We realize six AES designs based on the Sakura-X FPGA board, three designs embodying reported S-Box architectures and the other three designs leveraging on our multiplexing circuit and compensator. We show that our AES design, embodying our LUT based S-Box architecture with the AND/OR-gate multiplexing circuit and compensator, has the highest security feature (against CPA) compared with the reported designs, featuring 10× to 300× better security.